A força pública em Mato Grosso e a formação do corpo policial no período imperial - Martins, David Campos (Universidade do Vale do Rio dos Sinos, 2021)
This thesis intends to demonstrate how the formation of the Public Force occurred in the province of Mato Grosso, a process initiated in 1831 and which extended throughout the imperial period. The Public Force participated in the main local events, modifying the existing social relations and also suffering alterations by them. Managed by elites who pursued a supposed civility and urbanity in the period in question, but despite these aspects being desired, in fact little of them was obtained in the society of Mato Grosso. The institutions of force were the main responsible for leading to this desired civility, however, as they were ineffective, they ended up performing tasks more linked to inspection and coercion of the local population. Another important point is that in the province society was composed of very distinct and antagonistic social classes, especially blacks and slaves who were seen as a threat, but who, in fact, were essential for the functioning of local economic activities. This work, in addition to remounting the facts that involved the formation of the Public Force in the province, as the institutions are consolidating, seeks a more specific look at the bodies that exercised the police function, dealing with the everyday aspect of the forces. To analyze the Public Force in Mato Grosso, it is inevitable to enter the events of the War with Paraguay, which would be the main event in the province during the nineteenth century. Going back to events prior to the war, he comes to understand that the institutions of force in the province were problematic, which would be the main factor for the devastation of southern Mato Grosso in the foreign invasion. And finally, it is shown that in the post-war period, significant changes would take place in the Police Corps, which would remain until the end of the imperial period.
Keywords: Força pública; Polícia; Mato Grosso; Public force; Police; ACCNPQ::Ciências Humanas::História